Auditory Brainstem Response to Paired Click Stimulation as an Indicator of Peripheral Synaptic Health in Noise-Induced Cochlear Synaptopathy - Lee, Jae-Hun; Lee, Min Young; Choi, Ji Eun; Jung, Jae Yun (Frontiers in Neuroscience, 2021)
Introduction A defect in the cochlear afferent synapse between the inner hair cells and spiral ganglion neurons, after noise exposure, without changes in the hearing threshold has been reported. Animal studies on auditory evoked potentials demonstrated changes in the auditory brainstem response (ABR) measurements of peak Ⅰ amplitude and the loss of synapses, which affect the temporal resolution of complex sounds. Human studies of auditory evoked potential have reported ambiguous results regarding the relationship between peak Ⅰ amplitude and noise exposure. Paired click stimuli have been used to investigate the temporal processing abilities of humans and animals. In this study, we investigated the utility of measuring auditory evoked potentials in response to paired click stimuli to assess the temporal processing function of ribbon synapses in noise-induced cochlear synaptopathy. Materials and Methods Twenty-two Sprague Dawley rats were used in this study, and synaptopathy was induced by narrow band noise exposure (16 kHz with 1 kHz bandwidth, 105 dB SPL for 2 h). ABRs to tone and paired click stimuli were measured before and 1, 3, 7, and 14 days after noise exposure. For histological analyses, hair cells and ribbon synapses were immunostained and the synapses quantified. The relationships among ABR peak Ⅰ amplitude, number of synapses, and ABR to paired click stimuli were examined. Results Our results showed that ABR thresholds increase 1 day after noise exposure but fully recover to baseline levels after 14 days. Further, we demonstrated test frequency-dependent decreases in peak Ⅰ amplitude and in the number of synapses after noise exposure. These decreases were statistically significant at frequencies of 16 and 32 kHz. However, ABR recovery threshold to paired click stimuli increased which represent improvement in the ability of temporal auditory processing. Our results indicate that ABR recovery threshold is highly correlated with ABR peak Ⅰ amplitude after noise exposure. We also established a direct correlation between ABR recovery threshold and histological findings. Conclusions The result from this study suggests that in animal studies, the ABR to paired click stimuli along with peak Ⅰ amplitude has potential as an assessment tool for hidden hearing loss.